TAMI-69. NF1 MUTATION DRIVES NEURONAL ACTIVITY-DEPENDENT OPTIC GLIOMA INITIATION. (12th November 2021) - Pan, Yuan; Hysinger, Jared; Barron, Tara; Schindler, Nicki; Cobb, Olivia; Guo, Xiaofan; Yalçın, Belgin; Anastasaki, Corina; Mulinyawe, Sara; Ponnuswami, Anitha; Scheaffer, Suzanne; Ma, Yu; et al.
Abstract: Neurons have recently emerged as essential cellular constituents of the tumor microenvironment, where their activity increases the growth of a diverse number of solid tumors. While the role of neurons in tumor progression has been previously demonstrated, the importance of neuronal activity to tumor initiation is less clear, particularly in the setting of cancer predisposition syndromes. In the Neurofibromatosis-1 (NF1) cancer predisposition syndrome, in which tumors arise in close association with nerves, 15% of individuals develop low-grade neoplasms of the optic pathway (optic pathway gliomas [OPGs]), during early childhood, raising the intriguing possibility that postnatal light-induced optic nerve activity drives tumor initiation. Here, we employ an authenticated murine model of Nf1 -OPG to demonstrate that stimulation of optic nerve activity increases optic glioma growth, while decreasing visual experience via light deprivation prevents tumor formation and maintenance. We show that Nf1 -OPG initiation depends on visual experience during a developmental period susceptible to tumorigenesis. Germline Nf1 mutation in retinal neurons results in aberrantly high optic nerve neuroligin-3 (Nlgn3) shedding in response to retinal neuronal activity. Moreover, genetic Nlgn3 loss or pharmacological inhibition of Nlgn3 shedding blocks murine Nf1 optic gliomagenesis and progression. Collectively, these studies establish an obligate role for neuronal activity in the development of certain brain tumors, elucidate a therapeutic strategy to reduce OPG incidence or mitigate tumor progression, and underscore the role of Nf1 mutation-mediated dysregulation of neuronal signaling pathways in the NF1 cancer predisposition syndrome.